Effect of dietary supplementation of copepod meal in goldfish Carassius auratus (Linnaeus, 1758) on growth performance, fatty acid profile and colouration - Gumus, Erkan; Gurler, Cisem; Gulle, Iskender (Indian Journal of Fisheries, 2022)
This study assessed the use of copepod meal (Arctodiaptomus salinus) as a carotene source for colour enhancement in goldfish Carassius auratus (Linnaeus, 1758). The effect of copepod meal on growth and fatty acid profile of goldfish was also evaluated. Copepod meal with 4,338 µg g-1 of total carotene and 1,655.78 µg g-1 of β-carotene per gram dry weight was added to the diet containing 0 (control), 50, 150 and 300 µg g-1 of β-carotene. Four diets with similar protein (35.17% CP) and energy (3745 kcal g-1) levels were prepared. The fish were fed with diets twice a day for 60 days. The results showed that there was no statistically significant difference between body weight, total length, condition factor and survival rates of the groups fed on different diets. Body coloration measured in terms of L* a* b* values increased with the increase in level of copepod meal in the diet. In all experimental groups, copepod meal incorporated diets had a significant effect on the fish flesh fatty acid profile (p